2009
DOI: 10.1029/2009je003365
|View full text |Cite
|
Sign up to set email alerts
|

Sublacustrine depositional fans in southwest Melas Chasma

Abstract: Two depositional fan complexes have been identified on the floor of southwest Melas Chasma. The western fan complex is located near the center of an enclosed basin in southwest Melas Chasma and is composed of multiple lobes with dendritic finger‐like terminations. These fans are very flat and have a morphology unlike any other fan that has been previously identified on Mars. On the basis of the morphologic similarity of the western fan complex to the Mississippi submarine fan complex, we suggest that it may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
95
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(97 citation statements)
references
References 108 publications
2
95
0
Order By: Relevance
“…The model developed in this study shows that breaching can occur in any granular material with sufficient dilation potential. My work also provides a framework and motivation for considering the occurrence of breaching on the surfaces of other planets and moons (Dromart et al, 2007;Metz et al, 2009) where liquid and granular materials exist. Liquefaction slope failure is usually associated with clay-rich deposits; increase in shear stress in the deposit drives the elevation of pore pressures until the deposit liquefies and releases large volumes of sediments all in once (Terzaghi, 1956;Morgenstern, 1967;Lowe, 1976;Hampton et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The model developed in this study shows that breaching can occur in any granular material with sufficient dilation potential. My work also provides a framework and motivation for considering the occurrence of breaching on the surfaces of other planets and moons (Dromart et al, 2007;Metz et al, 2009) where liquid and granular materials exist. Liquefaction slope failure is usually associated with clay-rich deposits; increase in shear stress in the deposit drives the elevation of pore pressures until the deposit liquefies and releases large volumes of sediments all in once (Terzaghi, 1956;Morgenstern, 1967;Lowe, 1976;Hampton et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The lake subsequently drained toward north (Ori et al 2000;Chapman 2008, 2010;Lucchitta 2009;Metz et al 2009;Flahaut et al 2010;Lucchitta 2010;Sowe et al 2011;Warner et al 2013). Thus, depending on the timing of the lake disappearance in relation to the landslide events, it is possible that at least some of the most ancient landslides were subaqueous.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the surface of the lowlands in the northern hemisphere exhibits widespread indications of ice at higher latitudes (Mouginot et al 2012), only more recently has it been suggested that glacial conditions might have been achieved in the equatorial regions during some episodes of Mars Hesperian-Amazonian history (Head and Marchant 2003;Murray et al 2005;Fueten et al 2011;De Blasio 2011a;Gourronc et al 2014). Thus, different lines of evidence suggest that VM has been filled for a long period by subsurface or exposed ice (De Blasio 2011a;Gourronc et al 2014) or a lake (Ori et al 2000;Chapman 2008, 2010;Lucchitta 2009;Metz et al 2009;Flahaut et al 2010;Lucchitta 2010;Sowe et al 2011;Warner et al 2013;Fueten et al 2014). This work explores landslide morphologies also with the objective of providing more independent data on their depositional environment.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed site targets layered sedimentary beds deposited in a postulated paleolake that was fed by tributaries of Hesperian age (Dromart et al, 2007;Metz et al, 2009;Quantin et al, 2005). Some of the beds may have been deposited in sublacustrine fans (Metz et al, 2009) and the depositional setting suggests significant water was present and stable for at least hundreds to thousands of years (Metz et al, 2009).…”
Section: Narrowing the List Of Candidate Sitesmentioning
confidence: 99%